Optimalisasi Satuan Fungsi Intelkam Dalam Pelaksanaan Deteksi Dini Pada Pengajaran Radikalisme Di Wilayah Polres Ciamis - Pramardhia, Ezard (Indonesian Journal of Police Studies, 2017)
The spread of radicalism teaching is a problem in Kab. Ciamis, originated from the existence of a radical Islamic movement that wanted to establish the state of Indonesia to become an Islamic state so as to make people affected by the radicalist movement in Ciamis. For this reason, Sat Intelkam puts forward the Early Detection Act, the purpose of early detection is to find out the location of the spread of radicalism so that intelligence members can block the spread. In the discussion of this thesis the author uses Management theory (POAC), Management (6M), Radicalism Concepts, Optimization Concepts, and Promoter as a knife of analysis to discuss research findings and problems. This study uses a qualitative approach and type of research in the form of field research. The focus of research on Satkamkam in Ciamis Regional Police with the community in the District. Ciamis is the source of document data, then the validity of the data is proven by triangulating the data. Data analysis techniques include data reduction, data presentation and conclusion drawing. The results found the spread of radicalism in Ciamis was high. Early Detection Efforts analyzed by management theory are collecting information about dissemination, knowing the characteristics of the community, knowing the sources of teaching radicalism, and reporting it to the leadership in accordance with the main tasks of the Intelligence. Inhibiting factors, HR factors, time and place, community attention and support, while supporting factors in the form of budget and cross-sectoral cooperation. Based on the results of research, various efforts have been carried out in preventing the spread of teaching radicalism. The author recommends providing vocational education (Dikjur), adding personnel, and adding sarpras to support Early Detection activities to improve the effectiveness of the Ciamis Police Intelligence Unit performance.